PENGARUH PRILAKU MENYALAHKAN KORBAN DALAM TINDAK PIDANA KESUSILAAN DI INDONESIA - Muhammad Iqbal; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The culture of blaming the victim is so prevalent that many victims of sexual harassment are afraid to report their cases. Some victims may worry that they will be stigmatized. The victim is considered to have damaged the good name of the family or institution. They could even be criminalized for reporting acts of harassment or rape.The purpose of this study is to determine the behavior of blaming victims against law enforcement in Indonesia and to determine legal protection for victims of criminal acts of decency so that they do not become victims in the Indonesian Criminal Justice System. The research method used in this research is normative legal research method. The data obtained from this research are primary data, secondary data, and tertiary data which are processed qualitatively.Based on the results of this study, the provisions of the parties that provide protection for victim blaming victims (victims who are blamed) include, First, the state is considered as one of the important factors because the state has the authority and ability to guarantee the safety of victims. Second, community service providers, in fulfilling the victim's mental state, require community services. Third, society, in fact the community has enormous potential in providing protection and support for victims.Keywords: victim, blame the victim, law enforcement